Preliminary study on combustion of biodiesel for power generation - Tan E.S.; Palanisamy K.; Hussein I.; Ani F.N. (American Society of Mechanical Engineers (ASME), 2023)
In the recent wake of escalating crude oil prices due to depletion of fossil fuel, biodiesel has generated a significant interest as an alternative fuel for the future. The use of biodiesel to fuel microturbines or gas turbine application is envisaged to solve problems of diminishing supplies of fossil fuel reserves and environmental concerns. This paper examines the combustion of biodiesel derived from Malaysian Waste Cooking Oil (WCO) in a combustion test facility to study the feasibility of using the designated fuel at five various volumetric ratios for gas turbine application. Biodiesel was produced from waste cooking oil in Malaysia, mainly from palm oil sources and animal fats. The oil burner was able to fire the five blends of fuel without any modification or pretreatment. The combustion performance of Malaysian WCO biodiesel and distillate blends was examined with respect to the combustion efficiency. The results indicated biodiesel combustion required less air for stoichiometric combustion due to presence of oxygen in the fuel. Indeed biodiesel stand as a potential alternative fuel for power generation application with the best efficiency at blended ratio of 20% biodiesel and 80% distillate. Copyright 2006 by ASME.